2011
DOI: 10.4103/1319-3767.77243
|View full text |Cite
|
Sign up to set email alerts
|

Generalized peritonitis requiring re-operation after leakage of omental patch repair of perforated peptic ulcer

Abstract: Background/Aim:Peptic ulcer perforations are a common emergency, but available literature is silent on the exact definition, incidence, management, and complications of peritonitis due to omental patch leakage.Patients and Methods:Retrospective data were collected on 422 patients who underwent omental patch repair of perforated peptic ulcer between March 20, 1999 and March 20, 2006. The definitive diagnosis of perforated peptic ulcer and omental patch leakage was obtained at surgery.Results:Seventeen (4%) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
1
23
1
Order By: Relevance
“…13 Poor level of success was also found in the present study contrasting with the results of Maghsoudiet al where the authors obtained a success of arresting the re-leak in 13/17 patients. 11 Similarly, we found higher mortality in contrast to Wakayama et al wherein the authors found a mortality of only 5%.…”
Section: Discussionsupporting
confidence: 48%
“…13 Poor level of success was also found in the present study contrasting with the results of Maghsoudiet al where the authors obtained a success of arresting the re-leak in 13/17 patients. 11 Similarly, we found higher mortality in contrast to Wakayama et al wherein the authors found a mortality of only 5%.…”
Section: Discussionsupporting
confidence: 48%
“…Hamby et al described a simple apposition procedure for arresting the re-leak but inflammation and induration of the ulcer surroundings precludes this intervention [6] . Poor level of success of surgical intervention was found in our study which is in contrast with the results of Maghsoudi et al where the authors obtained a success of arresting the re-leak in 13/17 (76.5%) patients [7] .…”
Section: Discussioncontrasting
confidence: 99%
“…Postoperative complications are frequent, and include common diagnoses such as wound and other abdominal infections, thromboembolic events and organ failure. Rarer complications include omental patch leakage requiring reoperation in about 4 per cent of patients and persistent duodenal fistula.…”
Section: Resultsmentioning
confidence: 99%